THE EFFECT OF PEPPERMINT AROMATHERAPY ON NAUSEA AND VOMITING IN PREGNANT WOMEN IN THE FIRST TRIMESTER - S.Kep., M.Kep, Ns. Harismayanti; S.Kep., M.Kep, Ns. Ani Retni; SKM., M.Kes, Dr. Zuriati Muhamad; Katili, Sri Fahrin (Jambura Nursing Journal, 2025)
In the early stages of pregnancy, nausea and vomiting are known as emesis gravidarum. A common treatment for emesis gravidarum is aromatherapy; breathing peppermint might lessen nausea and vomiting. The purpose of this study is to ascertain the impact of aromatherapy peppermint on first-trimester nausea and vomiting in pregnant women in the Telaga Health Center working area. The study used a quantitative methodology and a pre-experimental design with a single group pre-test-post-test. Purposive sampling was used to choose the samples. Thirty individuals who were in the first trimester of pregnancy made up the entire sample. According to the study's findings, respondents had nausea and vomiting on average nine times per day prior to the intervention, but this frequency dropped to six times per day following the intervention. Peppermint aromatherapy had an effect on nausea and vomiting in first-trimester pregnant women in the Telaga Health Center working area, according to statistical analysis using the Wilcoxon signed rank test, which yielded a p value of 0.000 < 0.05. In conclusion, the typical patient experiences minor nausea and vomiting following aromatherapy. Suggestion: Aromatherapy is a non-pharmacological treatment that can be used as a guide to improve the quality of services for pregnant women who complain of nausea and vomiting during the first trimester.